Protein Docking Model Evaluation by Graph Neural Networks - Wang, Xiao; Flannery, Sean T.; Kihara, Daisuke (Frontiers in Molecular Biosciences, 2021)
Physical interactions of proteins play key functional roles in many important cellular processes. To understand molecular mechanisms of such functions it is crucial to determine the structure of protein complexes. To complement experimental approaches, which usually take a considerable amount of time and resources, various computational methods have been developed for predicting the structures of protein complexes. In computational modeling, one of the challenges is to identify near-native structures from a large pool of generated models. Here, we developed a deep learning-based approach named Graph Neural Network-based DOcking decoy eValuation scorE (GNN-DOVE). To evaluate a protein docking model, GNN-DOVE extracts the interface area and represents it as a graph. The chemical properties of atoms and the inter-atom distances are used as features of nodes and edges in the graph. GNN-DOVE was trained and tested on docking models in the Dockground database and further tested on a combined dataset of Dockground and ZDOCK benchmark as well as a CAPRI scoring dataset. GNN-DOVE performed better than existing methods including DOVE, which is our previous development that uses a convolutional neural network on voxelized structure models.